Challenges, strategies and innovation in managing information systems - Galliers, Robert D. (Bob) (Henry Stewart Talks, 2011)
Information systems (IS) and Information technology (IT), IT strategy, Agile information, Business process re-engineering (BPR), Knowledge management, Alignment
Updated at 2020/03/30